Darrieus vertical axis wind turbine for power generation II: Challenges in HAWT and the opportunity of multi-megawatt Darrieus VAWT development. (March 2015) - Tjiu, Willy; Marnoto, Tjukup; Mat, Sohif; Ruslan, Mohd Hafidz; Sopian, Kamaruzzaman
Abstract: This paper presents several multi-megawatt offshore Darrieus vertical axis wind turbine (VAWT) projects currently under way. The projects are re-attempting large scale VAWT since Eole, the only multi-megawatt Darrieus VAWT ever built, which was shut down in 1993. In addition, the project's timing is at the moment when horizontal axis wind turbine (HAWT) is facing major challenges in multi-megawatt range, especially for offshore wind power generation. The obstacles of large scale HAWT are elaborated, and the reasons of why Darrieus VAWT is key to the challenges are also explained. In addition, impacts of HAWT development on Darrieus VAWT are described. Lastly, the innovative designs on Darrieus VAWT are presented, which include current status of Sandia National Laboratories (SNL), novel offshore vertical axis (NOVA), Vertax and Vertiwind. Graphical abstract: Highlights: Assessment of major fundamental challenges in up-scaling HAWT. Assessment of Darrieus VAWT to overcome the challenges in up-scaling a HAWT. Assessment of Darrieus VAWT novel variations for offshore multi-megawatt application. Current development and future prospects of large scale Darrieus VAWT.